THE INFLUENCE OF FINANCIAL PERFORMANCE AND GOOD CORPORATE GOVERNANCE ON CSR DISCLOSURE MODERATED BY GROWTH - Utari, Lisa; Novitasari, Budi Tiara (Jurnal Ekonomi dan Bisnis Nias Selatan, 2023)
Corporate social responsibility (CSR) is an element that important not only for company but largely toward economics, environment, and society. However, in practice CSR Disclosure (CSRD) between companies is different. Thus, this research aims to determine the influence of financial performance (profitability, liquidity, leverage) and good corporate governance (foreign ownership, institutional ownership) on CSR disclosure moderated by growth on Indonesian companies in energy sector. Through purposive sampling method, the total sample uses is 22 companies while the data uses is 82 data were categorized as panel data. The data analysis techniques including statistic descriptive analysis, classical assumption test, and hypothesis test using moderated regression analysis panel data. The result of this research indicated that profitability, liquidity, and foreign ownership partially has significant positive influence on corporate social responsibility disclosure moderated by growth on energy sector companies in Indonesia. Meanwhile, leverage and institutional ownership partially has no positive influence on corporate social responsibility disclosure and growth could not moderated those relationship. Simultaneously, profitability, liquidity, leverage, foreign ownership, dan institutional ownership influence corporate social responsibility disclosure moderating by growth. This research provide additional knowledge about the factors that influence CSR in energy sector that will be beneficially to academics and practices in decision making to make a sustainable positive impact to the environment, the society, the state and the company itself.